Capacitor, flexible transparent carbon fiber net and electronic equipment

By growing cobalt complexes in situ on silk and heat treatment, a flexible transparent carbon fiber web was prepared, which solved the problem of damage to lithium-ion batteries after bending, and achieved flexible, transparent and high-performance batteries and capacitors.

CN119812293AActive Publication Date: 2025-04-11SHENGHONG KINETIC ENERGY TECH (TAIZHOU) CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510104309.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-04-11
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The battery modules of existing lithium-ion batteries have low tensile strain and insufficient flexibility. They are prone to damage after multiple bending tests, making it difficult to meet the energy supply needs of flexible foldable electronic devices.

Method used

By growing cobalt complexes in situ on silk and heat treatment at high temperatures, nitrogen-doped porous carbon-based electrode materials were prepared, and a flexible transparent carbon fiber web was prepared in combination with an acid etching method to make capacitors with excellent electrochemical properties and flexibility.

Benefits of technology

The flexible transparent electrode material of the battery and capacitor is realized, with good magnification, cycling performance and light transmittance, and can maintain a normal working state after multiple bends.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812293A_ABST
    Figure CN119812293A_ABST
Patent Text Reader

Abstract

The invention discloses a capacitor, a flexible transparent carbon fiber net and electronic equipment, and is characterized in that cobalt nitrate, imidazole and derivatives thereof are respectively applied to silk, cobalt complexes grow on the surface and / or in pores of the silk in situ to form silk loaded with the cobalt complexes, and then the silk loaded with the cobalt complexes is subjected to heat treatment in a protective atmosphere to obtain the flexible transparent carbon fiber net. The flexible transparent carbon fiber net can be prepared by further combining with acid etching; the flexible transparent carbon fiber net has excellent flexibility, electrochemical performance and light transmission, can be used as an electrode to be applied to a capacitor, and is beneficial to preparation of flexible portable electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention is a divisional application of the Chinese invention patent application with the application date of October 12, 2024, application number 2024114195070, and name “Electrode material and preparation method thereof, electrode, battery, flexible transparent carbon fiber mesh and preparation method thereof, capacitor, electronic device”. Technical Field

[0002] The present invention relates to the field of capacitor materials, and in particular to a capacitor, a flexible transparent carbon fiber mesh and an electronic device. Background Art

[0003] With the continuous development of science and technology, various types of portable electronic devices are playing an increasingly important role in daily life, and their functions are becoming more and more diversified. While improving the user experience, higher requirements are also placed on their energy supply and energy storage devices. Lithium-ion batteries have relatively mature production technology and higher energy density than other types of batteries. They can be repeatedly charged and discharged, and are environmentally friendly, making them the first choice for power sources for flexible wearable devices and mobile portable electronic devices. However, with the continuous improvement of user demand, one of the ultimate development directions of portable electronic devices may be flexible and foldable, which can further save space while ensuring user experience. This requires that its energy supply device should also have corresponding flexibility. However, the battery components of commercial lithium-ion batteries at this stage have low tensile strain and relatively insufficient flexibility, and are damaged after multiple bending tests. Summary of the Invention

[0004] The purpose of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved method for preparing a flexible transparent carbon fiber mesh having flexibility, excellent electrochemical properties and light transmittance, a flexible transparent carbon fiber mesh prepared therefrom, and a capacitor comprising the flexible transparent carbon fiber mesh.

[0005] The present invention also provides an electronic device comprising the capacitor, so that the electronic device has flexible and foldable properties.

[0006] To achieve the above object, the present invention adopts a technical solution: a method for preparing an electrode material, the preparation method comprising:

[0007] applying cobalt nitrate and the compound represented by formula (I) on silk respectively, and growing a cobalt complex in situ on the surface and / or in the pores of the silk to form silk loaded with the cobalt complex;

[0008] In which R1 and R2 are independently selected from C 1-3 Alkyl, n is 0, 1 or 2;

[0009] heat-treating the silk loaded with the cobalt complex at 700-950° C. under a protective atmosphere to obtain the electrode material;

[0010] The electrode material comprises nitrogen-doped porous carbon and nano-metal cobalt supported on the surface of the nitrogen-doped porous carbon and / or encapsulated in the pore structure of the nitrogen-doped porous carbon.

[0011] According to some preferred and specific aspects of the present invention, the preparation method further comprises:

[0012] Separately prepare a cobalt nitrate solution and a solution of the compound represented by formula (I);

[0013] The silk is first soaked in one of the cobalt nitrate solution and the solution of the compound represented by formula (I), and then soaked in the other one.

[0014] In some embodiments of the present invention, the cobalt nitrate solution and the solution of the compound represented by formula (I) respectively use water as solvent.

[0015] According to some specific aspects of the present invention, the molar concentration of the cobalt nitrate solution is 0.5-1.5 mol / L, for example, it can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, etc.

[0016] According to some specific aspects of the present invention, the molar concentration of the solution of the compound represented by formula (I) is 1.5-3.0 mol / L, for example, it can be 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L, 2.5 mol / L, 2.6 mol / L, 2.7 mol / L, 2.8 mol / L, 2.9 mol / L, 3.0 mol / L, etc.

[0017] According to some preferred aspects of the present invention, the silk is first soaked in the cobalt nitrate solution for X1 min, and then soaked in the solution of the compound represented by formula (I) for X2 min, with X1:X2=1.5-3:1.

[0018] In some embodiments of the present invention, X1 is 15-25, and X2 is 5-15.

[0019] In some embodiments of the present invention, R1 is selected from methyl, ethyl or propyl, and n is 0.

[0020] In some embodiments of the present invention, R1 and R2 are independently selected from methyl, ethyl or propyl, and n is 1 or 2.

[0021] According to some specific aspects of the present invention, the compound represented by formula (I) is a combination of one or more selected from 2-methylimidazole, 2-ethylimidazole, and 2-propylimidazole.

[0022] According to some preferred aspects of the present invention, the amount of cobalt nitrate added is controlled to load 0.015-0.05 mmol per square centimeter of the silk.

[0023] According to some preferred aspects of the present invention, the added amount of the compound represented by formula (I) is 0.03-0.1 mmol per square centimeter of the silk.

[0024] In some embodiments of the present invention, the silk is made of mulberry silk. According to a specific aspect of the present invention, the silk is commercial mulberry silk with a specification of 5.5 momme.

[0025] In some embodiments of the present invention, the preparation method further comprises: before performing the heat treatment, washing the silk loaded with the cobalt complex and performing a drying treatment.

[0026] In some embodiments of the present invention, the cleaning is performed using deionized water.

[0027] In some embodiments of the present invention, the drying process is vacuum drying. Furthermore, the drying process temperature is 50-70° C. Furthermore, the drying process time is 1-3 hours.

[0028] According to some preferred aspects of the present invention, the heat treatment is performed at 750-850°C.

[0029] In some embodiments of the present invention, the heat treatment time is 1-6 hours, further 1-3 hours.

[0030] According to the present invention, the nitrogen-doped porous carbon is a carbon fiber network structure formed by interweaving a plurality of carbon fibers.

[0031] According to the present invention, the electrode material is in a transparent state.

[0032] In some embodiments of the present invention, the diameter of the carbon fiber is 30-500 nm, further 100-200 nm.

[0033] Another technical solution provided by the present invention is an electrode material prepared by the above-mentioned method for preparing the electrode material.

[0034] Another technical solution provided by the present invention is an electrode, which comprises the electrode material described above.

[0035] Another technical solution provided by the present invention is a battery, comprising a positive electrode and a negative electrode, wherein either the positive electrode or the negative electrode is the electrode described above.

[0036] Furthermore, the battery is a lithium-ion battery.

[0037] Another technical solution provided by the present invention is a method for preparing a flexible transparent carbon fiber mesh, the method comprising:

[0038] applying cobalt nitrate and the compound represented by formula (I) on silk respectively, and growing a cobalt complex in situ on the surface and / or in the pores of the silk to form silk loaded with the cobalt complex;

[0039] In the example, R1 is C 1-3 Alkyl, R2 is H or C 1-3 Alkyl, n is 1 or 2;

[0040] heat-treating the silk loaded with the cobalt complex at 700-950° C. under a protective atmosphere to obtain an intermediate;

[0041] Then, the intermediate is subjected to acid etching to obtain the flexible transparent carbon fiber mesh.

[0042] Furthermore, the acid etching is carried out using hydrochloric acid. In some embodiments of the present invention, the molar concentration of the hydrochloric acid can be 0.5-3 mol / L, for example, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L, 2.5 mol / L, 2.6 mol / L, 2.7 mol / L, 2.8 mol / L, 2.9 mol / L, 3.0 mol / L, etc.

[0043] According to some specific aspects of the present invention, the acid etching time is controlled to be 10-60 minutes.

[0044] In some embodiments of the present invention, the flexible transparent carbon fiber mesh has a pore structure with a size of 20-30 nm.

[0045] In some embodiments of the present invention, the protective atmosphere is formed by introducing nitrogen and / or an inert gas.

[0046] Another technical solution provided by the present invention is a flexible transparent carbon fiber net made by the above-mentioned preparation method of the flexible transparent carbon fiber net.

[0047] Another technical solution provided by the present invention is a capacitor comprising a positive electrode, a negative electrode, and an electrolyte between the positive electrode and the negative electrode, wherein either the positive electrode or the negative electrode comprises the flexible transparent carbon fiber mesh described above.

[0048] Another technical solution provided by the present invention is an electronic device comprising the battery or the capacitor described above.

[0049] Furthermore, an electronic device including the battery or the capacitor described above can help to make a flexible and foldable portable electronic device or a wearable electronic device.

[0050] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0051] Silk is a common biomass material with a very large annual output. The structure of silk is composed of silk protein and sericin. Under high temperature conditions, the protein molecules are rearranged during the pyrolysis process. In the present invention, by controlling the temperature of the heat treatment, the protein molecules of silk are transformed into sp with a graphite-like crystal layer structure. 2 Hybridized carbon hexagonal structure, thus forming a conductive material, which also contains a high content of nitrogen;

[0052] The present invention supports a cobalt complex formed by cobalt and a nitrogen-containing imidazole compound on silk before heat treatment, and in particular uniformly deposits the cobalt complex on the surface and pores of silk fibers through an in-situ synthesis method. After heat treatment, not only can a transparent and flexible porous carbon-based electrode material be prepared, but the ligands of the complex and the silk can generate nitrogen-doped porous carbon during the calcination process, while the cobalt ions are reduced to nano-metal cobalt and supported on the surface of the porous carbon and / or encapsulated in the pore structure of the porous carbon. Furthermore, when the heat-treated electrode material is subjected to acid etching by etching, the prepared material is conducive to being used as an electrode in a capacitor.

[0053] The lithium battery prepared based on the above materials and / or methods has good rate and cycle performance, and has small polarization phenomenon; the material also exhibits good electrochemical properties, light transmittance and flexibility when used to prepare capacitors.

[0054] Furthermore, the present invention can achieve the following technical effects:

[0055] (1) The materials are readily available, the cost is low, the preparation process is simple, and it is suitable for large-scale production.

[0056] (2) As a transparent negative electrode for preparing lithium batteries, its initial reversible capacity can reach 1060mAh·g -1 The discharge voltage platform is 0.75V, and its cycle performance is excellent (at 4A·g -1 The battery capacity can still reach 1000mAh·g after 475 cycles at a current density of -1 above).

[0057] (3) As a transparent negative electrode to prepare transparent capacitors, the surface capacitance of the capacitor is as high as 0.227mF / cm 2 , and it can still maintain 78% of its initial capacity after 2000 cycles in the cycle stability test.

[0058] (4) In the bending test, after 200 bends, the electrode material, flexible transparent carbon fiber mesh, and capacitor made from the present invention can still work normally and are basically intact. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 Schematic diagram of the preparation process of the electrode material of the present invention;

[0060] Figure 2 The SEM and TEM images of the electrode material obtained after heat treatment during the preparation process of Example 1;

[0061] Figure 3 This is the XRD pattern of the electrode material obtained after heat treatment during the preparation process of Example 1;

[0062] Figure 4 This is a physical picture of the electrode material prepared in Example 1;

[0063] Figures 5 to 7 The performance diagram of the lithium battery prepared based on the electrode material obtained in Example 1; wherein, Figure 5 is the rate performance of the battery at different current densities, Figure 6 This is the battery cycle performance test diagram. Figure 7 It is the battery voltage-capacity curve;

[0064] Figure 8 TEM and HRTEM images of the flexible transparent carbon fiber mesh prepared in Example 5;

[0065] Figure 9 This is a performance diagram of a capacitor prepared based on the transparent carbon fiber mesh obtained in Example 5;

[0066] Figure 10A comparison chart of the capacitance of capacitors prepared from flexible transparent carbon fiber meshes obtained in different examples (Example 5-Example 8);

[0067] Figure 11 The graph of the capacitance of the capacitor prepared based on the carbon fiber mesh obtained in Comparative Example 1 versus the number of cycles;

[0068] Figure 12 This is a comparison diagram of the cyclic voltammetry curves of the capacitor constructed based on the flexible transparent carbon fiber mesh obtained in Example 5 after 200 bending cycles. DETAILED DESCRIPTION

[0069] The above scheme is further described below in conjunction with specific examples; it should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions adopted in the examples can be further adjusted according to specific requirements, and the implementation conditions not specified are generally the conditions in routine experiments.

[0070] Unless otherwise specified in the following examples, all raw materials were purchased from commercial sources or prepared by conventional methods in the art.

[0071] In the following description, silk refers to commercial mulberry silk with a specification of 5.5 momme, and both the cobalt nitrate solution and the 2-methylimidazole solution refer to aqueous solutions.

[0072] Example 1:

[0073] This example provides an electrode material and a preparation method thereof, and the preparation method of the electrode material comprises the following steps:

[0074] S1. First, prepare 30 mL of 1 mol / L cobalt nitrate solution, labeled as solution A, and then prepare 30 mL of 2 mol / L 2-methylimidazole solution, labeled as solution B.

[0075] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.

[0076] S3, washing the silk loaded with the cobalt complex with deionized water three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;

[0077] S4. The dried silk loaded with the cobalt-2-methylimidazole complex was placed in a tube furnace for heat treatment at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an electrode material.

[0078] Example 2:

[0079] This example provides an electrode material and a preparation method thereof, and the preparation method of the electrode material comprises the following steps:

[0080] S1. First, prepare 30 mL of 0.5 mol / L cobalt nitrate solution, labeled as solution A, and then prepare 30 mL of 1 mol / L 2-methylimidazole solution, labeled as solution B.

[0081] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.

[0082] S3, washing the silk loaded with the cobalt complex with deionized water three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;

[0083] S4. The dried silk loaded with the cobalt-2-methylimidazole complex was placed in a tube furnace for heat treatment at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an electrode material.

[0084] Example 3:

[0085] This example provides an electrode material and a preparation method thereof, and the preparation method of the electrode material comprises the following steps:

[0086] S1. First, prepare 30 mL of 0.75 mol / L cobalt nitrate solution, labeled as solution A, and then prepare 30 mL of 1.5 mol / L 2-methylimidazole solution, labeled as solution B.

[0087] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.

[0088] S3, washing the silk loaded with the cobalt complex with deionized water three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;

[0089] S4. The dried silk loaded with the cobalt-2-methylimidazole complex was placed in a tube furnace for heat treatment at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an electrode material.

[0090] Example 4:

[0091] This example provides an electrode material and a preparation method thereof, and the preparation method of the electrode material comprises the following steps:

[0092] S1. First, prepare 30 mL of 1.5 mol / L cobalt nitrate solution, labeled as solution A, and then prepare 30 mL of 3 mol / L 2-methylimidazole solution, labeled as solution B;

[0093] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.

[0094] S3, washing the silk loaded with the cobalt complex with deionized water three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;

[0095] S4. The dried silk loaded with the cobalt-2-methylimidazole complex was placed in a tube furnace for heat treatment at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an electrode material.

[0096] Example 5:

[0097] This example provides a flexible transparent carbon fiber mesh and a preparation method thereof, wherein the preparation method of the flexible transparent carbon fiber mesh comprises the following steps:

[0098] S1. First, prepare 30 mL of 1 mol / L cobalt nitrate solution, labeled as solution A, and then prepare 30 mL of 2 mol / L 2-methylimidazole solution, labeled as solution B.

[0099] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.

[0100] S3, washing the silk loaded with the cobalt complex with deionized water three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;

[0101] S4, heat-treating the dried silk loaded with the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;

[0102] S5. The intermediate is acid-etched using hydrochloric acid having a molar concentration of 1 mol / L for 30 minutes to obtain a flexible transparent carbon fiber mesh.

[0103] Example 6:

[0104] This example provides a flexible transparent carbon fiber mesh and a preparation method thereof, wherein the preparation method of the flexible transparent carbon fiber mesh comprises the following steps:

[0105] S1. First, prepare 30 mL of 0.5 mol / L cobalt nitrate solution, labeled as solution A, and then prepare 30 mL of 1 mol / L 2-methylimidazole solution, labeled as solution B.

[0106] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.

[0107] S3, washing the silk loaded with the cobalt complex with deionized water three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;

[0108] S4, heat-treating the dried silk loaded with the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;

[0109] S5. The intermediate is acid-etched using hydrochloric acid having a molar concentration of 1 mol / L for 30 minutes to obtain a flexible transparent carbon fiber mesh.

[0110] Example 7:

[0111] This example provides a flexible transparent carbon fiber mesh and a preparation method thereof, wherein the preparation method of the flexible transparent carbon fiber mesh comprises the following steps:

[0112] S1. First, prepare 30 mL of 0.75 mol / L cobalt nitrate solution, labeled as solution A, and then prepare 30 mL of 1.5 mol / L 2-methylimidazole solution, labeled as solution B.

[0113] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.

[0114] S3, washing the silk loaded with the cobalt complex with deionized water three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;

[0115] S4, heat-treating the dried silk loaded with the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;

[0116] S5. The intermediate is acid-etched using hydrochloric acid having a molar concentration of 1 mol / L for 30 minutes to obtain a flexible transparent carbon fiber mesh.

[0117] Example 8:

[0118] This example provides a flexible transparent carbon fiber mesh and a preparation method thereof, wherein the preparation method of the flexible transparent carbon fiber mesh comprises the following steps:

[0119] S1. First, prepare 30 mL of 1.5 mol / L cobalt nitrate solution, labeled as solution A, and then prepare 30 mL of 3 mol / L 2-methylimidazole solution, labeled as solution B;

[0120] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.

[0121] S3, washing the silk loaded with the cobalt complex with deionized water three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;

[0122] S4, heat-treating the dried silk loaded with the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;

[0123] S5. The intermediate is acid-etched using hydrochloric acid having a molar concentration of 1 mol / L for 30 minutes to obtain a flexible transparent carbon fiber mesh.

[0124] Comparative Example 1:

[0125] This example provides a carbon fiber mesh and a preparation method thereof, wherein the preparation method of the carbon fiber mesh comprises the following steps:

[0126] S1. Wash the silk without the cobalt-2-methylimidazole complex with deionized water three times, flatten it and dry it in a vacuum drying oven at 60 degrees Celsius for 2 hours.

[0127] S2, heat-treating the dried silk without the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;

[0128] S3, using hydrochloric acid with a molar concentration of 1 mol / L to acid-etch the intermediate for 30 minutes to obtain a carbon fiber mesh. Performance test:

[0129] The electrode material disclosed in the present invention is characterized by preparing a porous electrode structure through a simple and convenient in-situ synthesis of a cobalt-imidazole complex and then heat treatment. For the flexible transparent carbon fiber mesh, the preparation process further combines an acid etching method to prepare a porous transparent conductive carbon fiber mesh. They all have excellent electrochemical properties. When they are assembled into transparent lithium batteries and transparent capacitors, they all show good electrochemical performance. The electrode material is used as a transparent positive electrode to prepare a lithium battery (battery test: the positive electrode is made of the electrode material prepared by the present invention, the negative electrode is metallic Li, and the electrolyte is a mixed solution of EC ethylene carbonate / DEC diethyl carbonate in a volume ratio of 1:1 and LiPF6 is added, and the concentration of LiPF6 is 1 mol / L). Its initial reversible capacity reaches 1060mAh·g -1 , the discharge voltage platform is 0.75V; the cycle performance of the lithium battery is excellent, at 4A·g -1 The battery capacity can still reach 1000mAh·g after 475 cycles at a current density of -1 After the flexible transparent carbon fiber mesh was used as an electrode to prepare a capacitor (capacitor test electrolyte: ClNaO4 / PVA hydrogel), in the cycle stability test, the prepared capacitor was able to maintain 78% of its initial capacity after 2000 cycles. The initial surface capacitance of the capacitor was as high as 0.227mF / cm 2 In a bending test, the capacitor continued to function normally and remained intact after 200 bends. Compared with traditional preparation methods, this manufacturing process has the advantages of simple material preparation, readily available raw materials, and low cost, making it suitable for large-scale production.

[0130] Figure 1 Schematic diagram of the preparation process of the electrode material of the present invention. The electrode material of the present invention is prepared by in-situ synthesis and heat treatment.

[0131] For the flexible transparent carbon fiber mesh, an acid etching step is added compared to the preparation process of the electrode material. The flexible transparent carbon fiber mesh and NaClO4 / PVA hydrogel electrolyte can be constructed into a transparent supercapacitor.

[0132] Figure 2 The SEM and TEM images of the electrode material obtained after heat treatment during the preparation process of Example 1 are shown. Figure 2 As shown in Figure a), the electrode material has a carbon fiber mesh structure. The carbon fiber mesh is made of carbon fibers with a diameter of 100-200nm, and the fibers are evenly and orderly distributed. Figure 2 As shown in Figure b), when the carbon fiber mesh is partially enlarged, it can be clearly observed that the nanoparticles are evenly distributed.

[0133] Figure 3This is the XRD pattern of the electrode material obtained after heat treatment during the preparation process of Example 1, which is completely consistent with the diffraction peak position of metallic cobalt (PDF (standard diffraction card NO.): 00-015-0806), proving that a large number of metallic cobalt nanoparticles are deposited on the surface of the electrode material.

[0134] Figure 4 This is a physical picture of the electrode material prepared in Example 1. When it is placed on a paper with letters, it can be seen that the obscured letters can be clearly seen through the electrode material in the form of a carbon fiber mesh, proving that the electrode material has good transparency.

[0135] Figures 5 to 7 This is a performance diagram of a lithium battery prepared based on the electrode material obtained in Example 1;

[0136] in, Figure 5 The figure shows the rate performance of the battery at different current densities. As the current density increases, the specific capacity gradually decreases. In the first cycle, its initial reversible capacity reaches 1060 mAh g -1 As the rate increases, the specific capacity of the battery decreases significantly. When the current density returns to 1A·g -1 When the specific capacity is restored to 1100mAh·g -1 It shows that the battery has good rate recovery capability.

[0137] Figure 6 The battery cycle performance test diagram is shown in Figure 4A·g. -1 After 475 cycles at a current density of 1000 mAh g, the battery capacity can still reach 1070 mAh g -1 , showing relatively stable cycle performance;

[0138] Figure 7 The battery voltage-specific capacity curve is shown in Figure 2. During the first cycle, the charge-discharge curves show significant variation, indicating the formation of a solid electrolyte interface (SEI) film during the initial cycles. The curves for the second and third cycles overlap, indicating that the battery's electrochemical reaction is stabilizing, exhibiting good reversibility and minimal polarization.

[0139] Figure 8 The following are TEM and HRTEM images of the flexible transparent carbon fiber mesh prepared in Example 5. The TEM image is shown in Figure a) on the left, and the HRTEM image is shown in Figure b) on the right. As shown in the figures, after etching with hydrochloric acid, the carbon fibers form a rich porous structure with pores of approximately 20-30 nm, which effectively increases the specific surface area of ​​the flexible transparent carbon fiber mesh, effectively increases ion adsorption, and improves capacitance.

[0140] Figure 9 The performance diagram of the capacitor (NaClO4 / PVA hydrogel electrolyte) prepared based on the transparent carbon fiber mesh obtained in Example 5; wherein, Figure 9 Figure a) shows the cyclic voltammetry curves at different scan rates. The curve shape and area change with increasing scan rate, showing the electrochemical behavior of the capacitor at different scan rates. A higher scan rate leads to a larger current response, which is due to a faster charge / discharge process, indicating that the transparent carbon fiber mesh obtained by the present invention can be used to prepare capacitors; Figure 9 Figure b) is the cyclic voltammetry curve under different potential windows. It can be seen that as the potential window increases, the current response increases significantly, which is in line with the trend, further indicating that the transparent carbon fiber mesh obtained by the present invention can be used to prepare capacitors; Figure 9 Figure c) shows the cyclic voltammetry curves at different cycle numbers. As the cycle number increases, the shape and area of ​​the cyclic voltammetry curves do not change much, indicating that the capacitor maintains good electrochemical stability and reversibility after multiple cycles. Figure 9 Figure d) shows the change of capacitance with the number of cycles. The capacitance value gradually decreases with the increase of the number of cycles, from the initial about 221μF / cm 2 Reduced to about 172μF / cm 2 (2000 cycles), indicating that it has a long service life; Figure 9 Figure e) shows the constant current charge and discharge curves at different currents. Higher currents result in shorter charge and discharge times, indicating the fast response capability of the capacitor at high currents.

[0141] Figure 10 Comparison charts of the capacitance (current capacity) of capacitors prepared from flexible transparent carbon fiber meshes obtained in different embodiments (Examples 5-8) show that the capacitance first increases and then decreases with increasing immersion solution concentration, demonstrating the enhanced capacitance achieved by the porous structure and ion adsorption. However, excessive cobalt deposition combined with acid etching may damage the carbon fiber structure, thereby reducing capacitance.

[0142] Figure 11 The graph of the capacitance of the capacitor prepared based on the carbon fiber mesh obtained in Comparative Example 1 versus the number of cycles shows that the capacitance gradually decreases with the increase of the number of cycles, from an initial value of about 39 μF / cm 2 Reduced to about 27μF / cm 2 (2000 cycles) Compared with Example 5, the initial capacitance of the capacitor constructed with the carbon fiber mesh prepared without loading the cobalt complex is only about 17% of that of the supercapacitor constructed with the flexible transparent carbon fiber mesh prepared with loading the cobalt complex, and the stability is significantly reduced.

[0143] Figure 12This is a comparison of the cyclic voltammetry curves of the capacitor constructed based on the flexible transparent carbon fiber mesh obtained in Example 5 after 200 bends. It can be seen that after 200 bends, there is no significant difference in the electrochemical performance of the capacitor.

[0144] The above embodiments are intended only to illustrate the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made in accordance with the spirit of the present invention are intended to be covered by the scope of protection of the present invention.

[0145] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.

Claims

1. A capacitor comprising a positive electrode and a negative electrode, characterized in that: Either the positive electrode or the negative electrode comprises a flexible transparent carbon fiber mesh, and the preparation method of the flexible transparent carbon fiber mesh comprises: Applying cobalt nitrate and the compound represented by formula (I) on silk respectively, growing a cobalt complex in situ on the surface and / or in the pores of the silk, and forming silk loaded with the cobalt complex; In the example, R1 is C 1-3 Alkyl, R2 is H or C 1-3 Alkyl, n is 1 or 2; The cobalt complex-loaded silk is heat-treated at 700-950° C. under a protective atmosphere to obtain an intermediate; Then, the intermediate is subjected to acid etching to obtain the flexible transparent carbon fiber mesh; The flexible transparent carbon fiber mesh has a pore structure with a size of 20-30 nm.

2. The capacitor according to claim 1, characterized in that The intermediate comprises nitrogen-doped porous carbon and nano-metal cobalt supported on the surface of the nitrogen-doped porous carbon and / or encapsulated in the pore structure of the nitrogen-doped porous carbon.

3. The capacitor according to claim 2, characterized in that The nitrogen-doped porous carbon is a carbon fiber mesh structure formed by interweaving a plurality of carbon fibers; further, the diameter of the carbon fibers is 30-500 nm, preferably 100-200 nm.

4. The capacitor according to claim 1, characterized in that The method for preparing the flexible transparent carbon fiber mesh also includes: A cobalt nitrate solution and a solution of the compound represented by formula (I) are respectively prepared; the cobalt nitrate solution and the solution of the compound represented by formula (I) use water as a solvent; The silk is first immersed in one of the cobalt nitrate solution and the solution of the compound represented by formula (I), and then immersed in the other solution.

5. The capacitor according to claim 4, characterized in that The molar concentration of the cobalt nitrate solution is 0.5-1.5 mol / L, and the molar concentration of the solution of the compound represented by formula (I) is 1.5-3.0 mol / L; and / or, the silk is first immersed in the cobalt nitrate solution for X1 min, and then immersed in the solution of the compound represented by formula (I) for X2 min, X1:X2=1.5-3:1, X1 is 15-25, and X2 is 5-15.

6. The capacitor according to claim 1, characterized in that R1 is selected from methyl, ethyl or propyl, and R2 is selected from H, methyl, ethyl or propyl; and / or, the material of the silk is mulberry silk; and / or, the preparation method of the flexible transparent carbon fiber mesh also includes: before the heat treatment, using deionized water to wash the silk loaded with the cobalt complex, and vacuum drying it; and / or, the heat treatment is carried out at 750-850°C, and further, the treatment time is 1-6h, and further 1-3h.

7. The capacitor according to claim 1, characterized in that The amount of cobalt nitrate added is controlled to be 0.015-0.05 mmol per square centimeter of the silk, and the amount of the compound represented by formula (I) added is controlled to be 0.03-0.1 mmol per square centimeter of the silk; and / or the compound represented by formula (I) is a combination of one or more selected from 2-methylimidazole, 2-ethylimidazole, and 2-propylimidazole.

8. The capacitor according to claim 1, characterized in that The acid etching is performed using hydrochloric acid; further, the molar concentration of the hydrochloric acid can be 0.5-3 mol / L, preferably, the etching time of the acid etching is controlled to be 10-60 min; and / or, the protective atmosphere is formed by introducing nitrogen and / or inert gas.

9. A method for preparing a flexible transparent carbon fiber mesh, characterized in that: The preparation method comprises: Applying cobalt nitrate and the compound represented by formula (I) on silk respectively, growing a cobalt complex in situ on the surface and / or in the pores of the silk, and forming silk loaded with the cobalt complex; In the example, R1 is C 1-3 Alkyl, R2 is H or C 1-3 Alkyl, n is 1 or 2; The cobalt complex-loaded silk is heat-treated at 700-950° C. under a protective atmosphere to obtain an intermediate; Then, the intermediate is subjected to acid etching to obtain the flexible transparent carbon fiber mesh.

10. An electronic device, characterized in that: The electronic device comprises the capacitor according to any one of claims 1 to 8, or the flexible transparent carbon fiber net made by the method for preparing the flexible transparent carbon fiber net according to claim 9.

Citation Information

Patent Citations

  • ZIF-9-based porous carbon / carbon fiber composite material and preparation method thereof

    CN109192985A

  • Flexible electrode based on carbonized silk fabric and flexible battery

    CN111740075A

  • Universal multifunctional nitrogen-doped carbon nanotube / carbon fiber cloth preparation method

    CN112467153A

  • Co and N-doped carbon nanofiber compound for lithium-oxygen battery

    CN113497239A

  • Preparation method of NiCo-LDH / AgNWs / cotton fiber flexible electrode material with three-dimensional network structure

    CN115954215A